Removal of bemacid red dye by adsorption on sawdust and carbonized sawdust - Dijana Drljača; Dajana Dragić; Aleksandra Borković; Tatjana Botić; Radmila Jandrić (Zaštita Materijala)
Today, huge amounts of coloured wastewater, released into ecosystems are a big problem, because they have harmful effects on humans, the environment, as well as the aquatic environment. One of the common treatments for removing dyes from wastewater is the adsorption process, with an emphasis on the use of cheap adsorbents. Therefore, the subject of this paper is the possibility of removing the anionic dye bemacid red (BR) on wood biomass sawdust and carbonized sawdust. The experiments examined the equilibrium contact time, the effect of initial pH, the effect of adsorbent dose, as well as the effect of the initial adsorbate concentration on the process of adsorption. By applying linear kinetic models, it was found that the adsorption process follows a pseudo-second-order kinetic model. It was found that pH does not have a significant effect on adsorption onto carbonized sawdust. By examining the effect of the initial adsorbent dose, it was found that optimal adsorption requires twice the mass of sawdust compared to carbonized sawdust. The use of linear adsorption isotherms shows better agreement with the Freundlich model for both adsorbents. The maximum adsorption capacity for sawdust is 30.18 mg/kg, while for carbonized sawdust it is 74.60 mg/kg. Use of sawdust and carbonized sawdust can be an effective adsorbent for removing the dye bemacid red from wastewater, which is confirmed by the experiment on a real sample of wastewater. The obtained efficiency of dye removal from real wastewater for sawdust is 42.9 %, and for carbonized sawdust 95.1 %.